2017
DOI: 10.4236/tel.2017.73044
|View full text |Cite
|
Sign up to set email alerts
|

Tax Compliance, Income Distribution and Social Norms

Abstract: This paper studies the effect of income inequality on tax evasion. To discuss the topic, we present a simple model, based on Benabouand Tirole [1], that incorporates incentives for tax compliance such as punishment and fines, intrinsic motivation and social norms. Since we consider a regressive system of incentives to comply, income inequality increases the value of tax evasion although overall propensity to comply is unaffected. In this framework, we consider the hypothesis that social norms are group specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
1
3
0
1
Order By: Relevance
“…Furthermore, it is concluded that the unjust income distribution increases the tax gap. This result is consistent with the studies of Bloomquist (2003), Cansız (2015), Gioacchino and Patriarca (2017), Alp and Töngör (2018), Argentiero et al (2021), who suggested that inequality in income distribution increases tax non-compliance/tax evasion.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, it is concluded that the unjust income distribution increases the tax gap. This result is consistent with the studies of Bloomquist (2003), Cansız (2015), Gioacchino and Patriarca (2017), Alp and Töngör (2018), Argentiero et al (2021), who suggested that inequality in income distribution increases tax non-compliance/tax evasion.…”
Section: Discussionsupporting
confidence: 92%
“…Çalışmada adaletsiz gelir dağılımının vergi açığını artırdığı sonucuna da varılmıştır. Bu sonuç gelir dağılımındaki adaletsizliğin vergi uyumsuzluğunu/vergi kaçakçılığını artırdığını öne süren Bloomquist (2003), Cansız (2015), Gioacchino ve Patriarca (2017), Alp ve Töngör (2018), Argentiero vd., (2021) çalışmalarıyla uyumludur.…”
Section: Discussionunclassified
“…The comparative statics and dynamics of their model indicate that temporary shocks in individual intrinsic motivation and in tax enforcement factors might persistently change the social norm for compliance. Following Besley et al (2019), although in a static setting, Di Gioacchino and Patriarca (2017) show that group specific social norms increase the negative effect of income inequality on tax evasion, having a further regressive effect on disposable incomes. They suggest that policies aimed at increasing tax compliance could exploit the social norm effects and would be more effective if they also reduce segregation among social groups.…”
Section: Related Literaturementioning
confidence: 99%
“…They found that the first strategy had no significant network effects but that the second strategy (in-person audit) increased the compliance rate by approximately 2% among those that shared a tax preparer with a visited firm. 8 In this paper, we follow Di Gioacchino and Patriarca (2017) and consider two income groups whose monetary incentives for tax evasion are different. As in Di Gioacchino and Fichera (2020), and similarly to Hashimzade et al (2014Hashimzade et al ( , 2015Hashimzade et al ( , 2016, we focus on non-pecuniary costs and consider the pressure from neighbours (local peer effect) as the main driver of tax compliance.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation